Exceeding the therapeutic zone of proximal development as a clinical error - Stiles, William B. (2016)
The Assimilation of Problematic Experiences Scale (APES) summarizes a developmental continuum along which psychological problems progress in successful psychotherapy. The therapeutic zone of proximal development (TZPD) is the segment of the APES continuum within which the clients can proceed from their current APES level to the next with the therapist's assistance. It is the therapeutic working zone for a particular problem. As the client makes progress on a problem, its TZPD shifts up the APES. Theoretically, so long as the therapist's interventions remain within the TZPD, the client feels safe enough to work. However, when an intervention aims beyond the upper limit, the client will find it too risky and will reject or avoid the proposal. In this sense, exceeding the TZPD can be considered as a clinical error. This article presents examples of exceeding the TZPD and ways the error can be repaired.